Pengaruh Pembelajaran Nht Dan Stad MenggunakanMedia Audio Visual Terhadap Hasil Belajar Ipa SiswaKelas Viii Smp MUHAMMADIYAH 1 SurakartaTahun Ajaran 2015/2016 - SILFIANA, AULIYA; , Drs. Djumadi, M.Kes (2016)
This research purpose to reviewing the effect of NHT and STAD learning using audio-visual media on the learning outcomes IPA of eighth grade students at SMP Muhammadiyah 1 Surakarta. This type of research is true experimental with design experiment is posttest only control group desain. Data collection technique used documentation and tests. Sampling using random sampling. The research sample are VIIIA, VIIIB, and VIIIC. Data were analyzed using the Kruskal-Wallis test. The results showed that the group with the audio-visual media NHT average 79.14 results of their study, a group of audio-visual media STAD with the average results of their study 74.09, and the average lecture group learning results 73.01. The use of audiovisual media can help teachers in presenting the material so that the students are more interested in paying attention. Based on the analysis, with STAD NHT group difference of 5.10, with a conventional NHT group difference of 6.13, and the group with a conventional difference STAD 1.03. This research can be concluded that the NHT learning with audio-visual media most influence on student learning results, while STAD that use audio-visual media greater influence on student learning results than conventional learning.